Factors Affecting University Choice Behaviour in the UK Higher Education - Dean Heathcote; Simon Savage; Amin Hosseinian-Far (MDPI AG, 2020)
Although regulations and established practices in academia have focused on a data-rich model of performance information, both to evidence operational capability and to support recruitment, it is considered that this approach has been largely ineffective in addressing student choice behaviour. Historical studies, business, psychology, and technology theories have pointed to the oversimplification that a data-led strategy can result in for mapping human behaviour. In this case, decision processes of students are understood to be nuanced by a vast range of factors with variable relevance for everyone. The effort of the study is to address how Systems Thinking, related policy development, and associated enabling techniques can be applied to the field to provide both a deeper understanding of the dictates of student behaviour and, by extension, the appropriate foci for data provision, enabling comparative business performance assessment of Higher Education Providers. This research has followed the Design Science Research (DSR) methodology; the developed model has been successfully evaluated against the understanding of education practitioners in an interview consultation process of the methodology. The analysis of interview feedback and the development and refinement of the proposed model generate the principle findings of the study. The model outlines the factors that might affect students' choices in the UK Higher Education.